2003
DOI: 10.1088/0953-8984/15/9/202
|View full text |Cite
|
Sign up to set email alerts
|

The relaxational properties of compositionally disordered ABO3perovskites

Abstract: Random lattice disorder produced by chemical substitution in ABO3 perovskites can lead to the formation of dipolar impurities and defects that have a profound influence on the static and dynamic properties of these materials that are the prototypical soft ferroelectric (FE) mode systems. In these highly polarizable host lattices, dipolar entities form polar nanodomains whose size is determined by the dipolar correlation length, rc, of the host and that exhibit dielectric relaxation in an applied ac field. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
618
3
13

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(678 citation statements)
references
References 72 publications
44
618
3
13
Order By: Relevance
“…As reported, the activation energy for dipolar relaxation in ferroelectrics is about 100~400meV (Samara, 2003). Therefore, the relaxation process with the activation energy of 230 meV in our samples may be a kind of dipolar relaxation process related to oxygen vacancies.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…As reported, the activation energy for dipolar relaxation in ferroelectrics is about 100~400meV (Samara, 2003). Therefore, the relaxation process with the activation energy of 230 meV in our samples may be a kind of dipolar relaxation process related to oxygen vacancies.…”
supporting
confidence: 62%
“…The relationship between the logarithm of measuring frequency and the reciprocal of T m is nearly linear. It is suggested that the relationship between the measuring frequency and T m following the Arrehenius law, which can be expressed as (Samara, 2003) …”
mentioning
confidence: 99%
“…We assume a close relationship to the dynamic behavior of PNR's, which are believed to be at the heart of the relaxor behavior. 1,28 We should notice that the nearly vertical line is close to the Vogel-Fulcher temperature T VF , where the PNR's size strongly changes 29 and above which the PNRs are dynamic ͑T VF is always close to the ZFHaFC line, which marks the disappearance of macroscopic metastable ferroelectric states͒. At low bias fields, the phase transition is diffuse due to coupling between Q and random fields.…”
Section: Resultsmentioning
confidence: 78%
“…Co 3+ acceptor ions are incorporated into the Ti 4+ -lattice site because of their similar ionic radii and oxygen vacancies are generated in order to compensate the valence. The resultant acceptor-oxygen vacancy dipoles in highly polarizable lattice can form either polar nanoregions (PNRs) like in ferroelectric relaxors [22][23][24] or can result in an internal bias which is formally equivalent to the energy difference of the dipolar defects between the accessible directions of the spontaneous polarization and affects the dielectric response [25][26][27]. Due to high polarizability of the ABO 3 lattice the dipolar defects polarize the neighboring part of the lattice forming the polar nanoregions the size of which is determined by temperature -dependent correlation length of the host.…”
Section: Introductionmentioning
confidence: 99%